Association of placental position with the development of hypertension in pregnancy - A., Prathima; P., Reddi Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorders remain the most common medical complication during pregnancy and contribute greatly to maternal and perinatal morbidity and mortality. Several tests have been proposed to identify the women at risk of developing hypertension. Among the various predictors, the placental location by USG at 18-24 weeks is cost effective, non- invasive and has a good positive predictive value. The present study was undertaken to predict the association of placental location with the development of hypertension in pregnancy. Methods: This was a longitudinal cohort study conducted on 380 uncomplicated primigravid women who attended the obstetric OPD of MGMC&RI over a period of 18 months (March 2017-august 2018). A detailed history was taken, and examination done and B.P. was measured. The placental location was determined by ultrasound at 18-24 weeks and the patients were divided into two groups : group A were women with lateral placenta and group B were women with other placental locations. All women were followed up for signs and symptoms of hypertensive disorders of pregnancy and mode of delivery and neonatal outcome were noted. Results: Out of 380 women, 56(14.7%) had lateral placenta and 324(85.3%) had other placental locations. Out of the 57 women who developed hypertensive disorders in pregnancy, 16(28.6%) had lateral placenta and 41(12.7%) had other placental locations. The risk of developing hypertension in pregnancy with lateral placenta was 3.5(odds ratio) with a 95% confidence interval (1.4-8.6). The sensitivity, specificity, positive predictive value and negative predictive value when placental laterality is used as a predictive test was 28.1%, 87.6%, 28.6% and 87.4% respectively. Conclusions: The placental laterality as determined by ultrasound at 18-24 weeks is a simple, non-invasive, cost-effective predictive test to predict women at high risk of developing hypertensive disorders of pregnancy and this test has a high specificity and negative predictive value.